Incentive Solutions - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2004)
This paper reviews the research literature relevant to economic development incentives provided by state and local governments, and recommends reforms in these incentives. I argue that the main problem with current incentive policies is that state and local governments often provide incentives that are not in the best interest of that state or local area, for example that are excessively costly per job created, or that provide jobs that do not improve the job opportunities of local residents. I suggest that reforms should be "bottom-up" rather than "top-down." Regulation of incentives by the federal government, or by international trade treaties, may prevent both desirable and undesirable incentives. "Bottom-up" reforms would include more information on incentive offers, a budget constraint on the volume of incentives, stronger standards for job quality, accessibility, and performance in incentives, and better benefit-cost analyses of incentives.
Additional information: A revised version of this paper titled "Solving the Problems of Economic Development Incentives" appears in Growth and Change, 36(2), Spring 2005.
Keywords: R58; R38; H71; 330; economic; development; incentives; local; regional; Bartik; solutions